Brief interpretations - a study in the method The Jalalayn and the interpretation of Safwa Al-Bayan for the meanings of the Qur’an by Sheikh Hassanein Makhlouf) as a model (Journal of the College of Basic Education, 2022)
The scholars of the Islamic nation left us abundant knowledge and a great heritage from the legacy of the Prophet, may God’s prayers and peace be upon him, so the result of their blessed efforts was a large group of valuable commentary books, including what is lengthy and elaborate, such as the interpretation of (Jami’ al-Bayan fi Tafsir Ayat al-Qur’an) by Abu Jaafar Muhammad ibn Jarir al-Tabari (224 AH - 313 AH). It is thirty parts, and the interpretation of Al-Razi (543 AH - 606 AH), which is a scientific approach based on the miraculous rhetorical method, and on the other hand there were brief interpretations, distinguished by accuracy in meaning, and brevity in the building, such as the examples of the interpretation of Jalalain, I mean by that Jalal al-Din al-Mahalli (d. (911 AH), and they are among the most famous brief interpretations, despite their small size. Scholars wrote about them more than nineteen authors in precise detail and criticism, so large and numerous footnotes and important comments appeared.